Transition delay and drag reduction using biomimetically inspired surface waves - Bhatia, D.; Li, G.; Lin, Y.; Sun, J.; Barrington, P.; Li, H.; Wang, J. (2020)
This paper explores the use of Two-Dimensional sinusoidal surface features to delay transition and/or reduce drag. The authors, in this paper demonstrated that the presence of low amplitude sinusoidal surface features might damp the disturbances in the laminar boundary layer, reduce wall shear stress and maintain laminar flow for longer than a conventional flat plate. The hypothesis of the paper is inspired by the simplification of the dermal denticle on the surface of the shark-skin. Simulations are carried out using the Transition SST model in FLUENT based on the evidences of the transition model being suitable for a wider variety of high curvature scenarios. The surface waves are simulated for different amplitudes and wavelengths and their impact on transition onset and drag reduction are quantified at different velocities. Results presented in this paper indicate that a transition delay of 10.8% and a drag reduction of 5.2% are achievable. Furthermore, this paper adds credence to the notion that biomimicry is a very promising avenue for future drag reducing methods.